Sex Offenses Perpetrated Against Older Adults: A Multivariate Analysis of Crime Scene Behaviors - Almond, Louise (Journal of interpersonal violence, 2022)
The aim of this study was to thematically explore the relationship between crime scene behaviors and background characteristics of offenders who commit sexual offenses against female victims aged 60 years or more. Research and understanding of offense behaviors in this area is extremely limited; therefore, the study sought to provide a preliminary understanding and multivariate model of offense behaviors in cases where older female adults were sexually abused. Twenty-seven crime scene behaviors from 143 rape or attempted rape cases of an older adult victim were analyzed; frequency data were computed to provide base rate information, and Smallest Space Analysis provided a visual representation of the co-occurrence of crime scene behaviors. Three distinct dominant themes were identified, in which 56% of offenses displayed themes of Involvement (22%), Control (17%), and Hostility (16%). The relationship between each dominant theme and selected background characteristics was then analyzed. For example, offenders displaying an Involvement theme were found to be significantly less likely to have prior convictions. Significance was also found in the relationship between dominant themes and a ?theft and kindred offence other? preconviction background characteristic. The findings demonstrate offending behavior can be separated into three distinct themes, providing an explanation of offender subtypes and supporting previous models found in other types of sexual offending. Applications for law enforcement agencies regarding identified themes and links with likely offender background characteristics are highlighted. Limitations and future research avenues are discussed.